Optimasi Travelling Salesman Problem With Time Windows Pada Sistem Rekomendasi Tujuan Wisata Di Kota Batu Dengan Metode Evolution Strategies - Dicky Manda Putra Sidharta; Nurul Hidayat; Edy Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Tourism has an important contribution in the Indonesian economy. City of Batu is one of the place that have a great tourism potential. Having a cool characteristic of the weather becomes one of the more values for city of Batu. Batu has various tourist destinations, both natural and artificial tourism. Many choices of tourist destinations is a good thing for tourists. On the other side, because of the many choices of tourist destinations, can cause tourists difficult to divide travel time in accordance with expectations. The problem is often experienced by tourists is when they want to visit a tourism place, but did not have time to visit the other one. Tourists need to have an overview of the travel route in order to get an effective tour schedule. Looking for the best travel route with minimum cost, but it can visit some tourist places optimally. Looking for the best tour route considering time variables can be called Traveling Salesman Problem With Time Windows (TSP-TW). TSP-TW can be solved by using a method in the concept of Evolutionary Algorithm, Evolution Strategies (ES). Based on the results of tests that have been done using the following parameters are the number of population size is 90, the number of offspring is 7Âµ, and the number of generation is 6, that generate the highest fitness value of 0,0011223345. The final result obtained in this research is an optimal tourist route in the city of Batu.